2012
DOI: 10.1248/cpb.60.348
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Selenium Species in Extract from Niboshi (a Processed Japanese Anchovy)

Abstract: Fish are selenium rich foodstuffs and a major selenium source for the Japanese population. Niboshi is processed from Japanese anchovy (Engraulis japonicus) and commonly used to prepare soup stock for Japanese dishes. In this study, we characterized selenium species in the Niboshi extract by ultrafiltration, ion-exchange chromatography and mass spectrometry. Selenium species in the Niboshi were more extractable by polar solvents (water and ethanol) than an apolar one (hexane) along with amino acids and proteino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Selenium in Asari and its Extract The selenium concentration of the lyophilized Asari meat (an edible part) was 4.34±0.48 μgSe/g which was higher than that of Niboshi, processed Japanese anchovy (1.21±0.03 μgSe/g), Shijimi clam (3.51±0.12 μgSe/g) or other foodstuffs. [29][30][31] The determination of selenium in lyophilized Asari meat indicated the dry-mass dependent increase of the total selenium amount in the Asari meat (Fig. S2).…”
Section: Resultsmentioning
confidence: 96%
“…Selenium in Asari and its Extract The selenium concentration of the lyophilized Asari meat (an edible part) was 4.34±0.48 μgSe/g which was higher than that of Niboshi, processed Japanese anchovy (1.21±0.03 μgSe/g), Shijimi clam (3.51±0.12 μgSe/g) or other foodstuffs. [29][30][31] The determination of selenium in lyophilized Asari meat indicated the dry-mass dependent increase of the total selenium amount in the Asari meat (Fig. S2).…”
Section: Resultsmentioning
confidence: 96%
“…We reported that the Niboshi extract contained ionic organoselenium species with a molecular mass less than 5,000 (Yoshida, et al, 2012). As a result of ion-pair extraction with HTAC and the following mass spectrometric analysis, the selenium isotopic pattern at m/z 577 with the 80 Se ion peak was detected.…”
Section: Separation Of Selenium Species In the Niboshi Extractmentioning
confidence: 98%
“…In the Japanese diets, Niboshi (~1 μgSe/g) is a commonly used foodstuff that is processed from the Japanese anchovy (Engraulis japonicus), and its extract is used as a general base seasoning for a wide variety of Japanese cuisines, just like the fumet de poisson and/or fond de veau for the French cuisine. We have previously shown that selenium from the Niboshi and its extract could restore the activity of the hepatic cellular GPx in dietary selenium-deficient mice, and the ionic organic compound with a molecular mass of less than 5,000 was the major selenium species in the Niboshi extract (Haratake, Takahashi, Ono, & Nakayama, 2007;Yoshida, Haratake, Fuchigami, & Nakayama, 2012). In this study, the authors addressed the in vitro assessment of the bioavailability of partially purified selenium species from the Niboshi extract using cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Niboshi (a processed Japanese anchovy, Engralus japonicus) extract was characterised for preparing Se-supplements. 230 Polar solvents (water and ethanol) were selected for extracting Se-species from Niboshi. Only 6 to 12% of the total selenium in the Niboshi was extracted using these solvents.…”
Section: Seleniummentioning
confidence: 99%